3y = 2x + 6
x + y = 7
y = 7 - x
3(7 - x) = 2x + 6
21 - 3x = 2x + 6
21 - 6 = 2x + 3x
15 = 5x
15/5 = x
3 = x
x + y = 7
3 + y = 7
y = 7 - 3
y = 4
Solution is (3,4)
Answer:
147
Step-by-step explanation:
7*7*3 = 147
volume of a rectangular prism = length*width*height, in this case, 7*7*3
hope this helps :)
Substitute first Y for the second Y
So it would be x + x + 6 = -2
Then it would be 2x +6 = -2
Move the 6 over so it would be 2x =-8
Divide by 2 your answer is x = -4
Answer: 35000/20000=1.75 pound
Step-by-step explanation: